Promoting Awareness of the Body's Centre in Classical and Modern Dance Training - Vītola, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Based on dance theorist insights into the basic components that determine performance of movements in dance, the article analyses promotion of a sense of bodily centre in classical and modern dance training. The most significant condition for a dancer to be able to fit within the confines of the proposed tasks in dance is to govern own body, which is made easier through an understanding of the body’s centre of gravity. Promoting an awareness of muscle activity being fixated within the central point of the body develops an understanding of movements around this point among dancers, which leads to easier control over performed movements. The article aims to analyse the awareness of the body’s centre among dancers and to justify its significance in classical and modern dance training. The article applies the theoretical research method – it characterises classical and modern dance and analyses the sense of body centre in dance.